2021
DOI: 10.1038/s41598-021-87414-5
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and genetic diversity of invasive Fall Armyworm after 2 years of introduction in India

Abstract: Fall Armyworm (FAW), Spodoptera frugiperda, is a polyphagous pest capable of feeding over 80 plant species and was indigenous to the Western Hemisphere. Within a span of 4 years, FAW has established itself throughout most of the regions in Africa and Asia causing significant losses in maize production. Owing to its revamped distribution range, it would be prudent to analyze the ensuing genetic changes and study the emerging phylogeographic patterns across the world. In this regard, we would like to provide a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 43 publications
9
22
0
Order By: Relevance
“…Therefore, the hybrid ( Tpi -C/ COI -R) was predominant, but the homogenous corn strain ( Tpi -C/ COI -C) was a minor genetic group in our survey. This result is similar to previous studies wherein the Tpi gene is a predictable molecular marker compared with the COI gene for the diagnosis of the FAW strain associated with host plant preference [ 15 , 16 , 17 , 44 ]. Another study in Myanmar and Southern China indicated that most of the strain is hybrid ( Tpi -C/ COI -R) [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, the hybrid ( Tpi -C/ COI -R) was predominant, but the homogenous corn strain ( Tpi -C/ COI -C) was a minor genetic group in our survey. This result is similar to previous studies wherein the Tpi gene is a predictable molecular marker compared with the COI gene for the diagnosis of the FAW strain associated with host plant preference [ 15 , 16 , 17 , 44 ]. Another study in Myanmar and Southern China indicated that most of the strain is hybrid ( Tpi -C/ COI -R) [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…Both Tpi -C/ COI -C and a hybrid strain ( Tpi -C/ COI -R) are similarly distributed in Central Africa, but a hybrid strain predominates in Eastern Africa. Further studies indicated that the hybrid strain predominates in South Africa and India [ 15 , 44 ]. The rice strain ( Tpi -R/ COI -R) is found in the Western Hemisphere, but it is rare in Africa [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FAW was first detected in India in 2018 in maize fields of Karnataka state [4], and quickly invaded other regions in India [9]. FAW is a highly destructive polyphagous crop pest with the greatest yield losses projected in maize [10,11].…”
Section: Introductionmentioning
confidence: 99%